Answer:
k = -2
Step-by-step explanation:
2 way to solve:
1st: 8x²-13x-4k = 8(x²-(13/8)x-(k/2))
if 2 roots: a and 1/a
8(x-a)(x-1/a) = 8(x²-(13/8)x-(k/2))
x²-(a+1/a)x+1 = x²-(13/8)x-(k/2)
1 = -(k/2)
<u>k = -2</u>
<u>2nd:</u> 2 roots of 8x²-13x-4k x=(-b±√b²-4ac)/2a
x = (13±√169-4*8*(-4k))/16 = (13±√169+128k)/16
(13+(√169+128k))/16 = 16/ (13-(√169+128k)) ... root1=1/root2
(13+(√169+128k))*(13-(√169+128k)) = 16*16
13² - (√169+128k)² = 256
169-169-128k = 256
-128k = 256
k = -2
If y = 0.75 when x = 0.5, set up a proportion -
0.75:0.5
x:3
Since you have to multiply 0.5 by 6 to get 3, multiply 0.75 by 6 to get your answer: y = 4.5 when x = 3.
It would look like this
when the sign has a line under it (>) the circle is closed and is a solid line. when there is no line under > its open and dotted.its -3 so you put the dot on -3. if x is greater than(in which this case it is)fill in the line greater than -3.
hope this helped!!
7 is option C
8 is option A
Answer:
8x
Step-by-step explanation:
10x-2x=8
8x